Locating women indigenous knowledge within the policy framework. (2000)
Rapid changes in the way of life of local communities and the consequent loss of indigenous knowledge, coupled with the increasing awareness that indigenous knowledge can play an important role in enhancing development, have led development workers in both governmental and non-governmental organizations to collect indigenous knowledge. Rural development policies and practices are now focusing on how indigenous knowledge could be incorporated on the policy framework of development.